Murine γδ T Lymphocytes Elicited during Plasmodium yoelii Infection Respond to Plasmodium Heat Shock Proteins - Kopacz, Jeffrey (American Society for Microbiology, 1999)
γδ T cells accumulate during Plasmodium infections in both murine and human malarias. The biological role of these cells and the antigens that they recognize are not clearly understood, although recent findings indicate that γδ T cells in general influence both innate and antigen-specific adaptive host responses. We examined the accumulation of γδ T cells elicited during infection with virulent and avirulent Plasmodium yoelii parasites in relatively susceptible and resistant strains of mice. Our results indicated that in nonlethal malaria infections, γδ T cells comprise a larger proportion of splenic T cells than in lethal infections and that only a live infection is capable of inducing an increase in the percentage of γδ T cells in vivo. Furthermore, we demonstrate that γδ T cells elicited during a P. yoelii infection respond by proliferation in vitro to P. falciparum heat shock proteins (HSPs) of 60 and 70 kDa, suggesting a possible immunological involvement of parasite HSPs in this arm of the cellular immune response during malarial infection in mice.